ANALYSIS OF THE INFLUENCE OF EMPLOYEE PERFORMANCE AND WORK PROGRAM PREPARATION ON THE QUALITY OF FINANCIAL PERFORMANCE - Erari, Klemens Simson Thomas; Sabandar, Sita Yubelina; Malissa, Mika (Entrepreneurship Undergraduate Program at Amkop Business School, 2025)
This study examines the impact of employee performance and work program planning on financial performance quality at BAPPEDA Kabupaten Nabire. Employing a quantitative approach, the research utilizes primary and secondary data from 43 employees. Data collection methods include observation, interviews, and documentation, while data analysis is conducted using Multiple Linear Regression with SPSS Version 22. The findings indicate that employee performance positively and significantly influences financial performance quality, with key factors including work quality, work quantity, responsibility, teamwork, and initiative. However, work program planning does not directly impact financial performance, suggesting that while structured programs exist, their effectiveness in enhancing financial outcomes remains uncertain. Nevertheless, employee performance and work program planning jointly exert a significant influence on financial performance quality. Effective management of these factors can optimize financial and developmental goals, ultimately benefiting the community in Nabire District.